A multiple regression model of normal central and peripheral motor conduction times. Issue 5 (14th March 2015) - Jaiser, Stephan R.; Barnes, Jonathan D.; Baker, Stuart N.; Baker, Mark R.
ABSTRACT: Introduction: The effects of age, height, and gender on magnetic central and peripheral motor conduction times (CMCT, PMCT) were analyzed using a multiple regression model. Methods: Motor evoked potentials were recorded in 91 healthy volunteers. Magnetic stimulation was performed over the primary motor cortex (cortical latency) and over the cervical and lumbar spines (spinal latency). The spinal latency was taken as an estimate of PMCT and was subtracted from cortical latency to yield CMCT. Results: Lower limb CMCT correlated significantly with height only; there were no significant predictors for upper limb CMCT. Upper and lower limb PMCT correlated with both age and height. Conclusions: This is among the largest studies of CMCT in normal subjects. The multiple regression model unifies previously reported simple regression analyses, reconciles past discrepancies, and allows normal ranges to be individualized. Muscle Nerve 51 :706–712, 2015